Genes Associated with Biological Nitrogen Fixation Efficiency Identified Using RNA Sequencing in Red Clover (Trifolium pratense L.) - Vlk, David; Trněný, Oldřich; Řepková, Jana (Life (Basel, Switzerland), 2022)
Commonly studied in the context of legume-rhizobia symbiosis, biological nitrogen fixation (BNF) is a key component of the nitrogen cycle in nature. Despite its potential in plant breeding and many years of research, information is still lacking as to the regulation of hundreds of genes connected with plant-bacteria interaction, nodulation, and nitrogen fixation. Here, we compared root nodule transcriptomes of red clover (Trifolium pratense L.) genotypes with contrasting nitrogen fixation efficiency, and we found 491 differentially expressed genes (DEGs) between plants with high and low BNF efficiency. The annotation of genes expressed in nodules revealed more than 800 genes not yet experimentally confirmed. Among genes mediating nodule development, four nod-ule-specific cysteine-rich (NCR) peptides were confirmed in the nodule transcriptome. Gene duplication analyses revealed that genes originating from tandem and dispersed duplication are significantly over-represented among DEGs. Weighted correlation network analysis (WGCNA) organized expression profiles of the transcripts into 16 modules linked to the analyzed traits, such as nitrogen fixation efficiency or sample-specific modules. Overall, the results obtained broaden our knowledge about transcriptomic landscapes of red clover's root nodules and shift the phenotypic description of BNF efficiency on the level of gene expression in situ.
Keywords: transcriptome; nodule-specific cysteine-rich peptide; differentially expressed gene; gene duplication